Marketing analysis of the Villány wine region - Törökné Kiss, Klára (Acta Agraria Debreceniensis, 2014)
Hungarian wine is not in such a bad position as it is considered. We have outstanding specialists and the country’s natural conditions are also proper. In Hungary, there are wine production and wine consumption has a major traditions. The role of marketing in our wine industry is growing more and more, and this trend is expected to continue in the future. The development of tourism in wine-growing regions and advertising would considerably promote the popularity of Hungarian wine.